DIRECTIONS OF DEVELOPMENT OF LEARNING MANAGEMENT SYSTEMS - YAREMKO, SVITLANA; KUZMINA, OLENA; BEVZ, SVITLANA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article considers the concept of a learning management system; examines the principles of a learning management system; highlights the features of Learning Management Systems; provides an analytical review of the most common learning management platforms. The article reveals a comparative analysis of both commercial and free integrated electronic management systems of the educational process with electronic management systems of their own development of higher educational institutions, as well as their functional capabilities in management educational process and their characteristics. Known educational management systems the process is focused on supporting the main functions of training. When analyzing the scientific literature on the development of control systems, we found that many scientists have dealt with this problem. The article discusses in detail the most popular learning management systems. We found that most users had such management systems as: Moodle, Claronline, ATutor, Mindflash, SkyPrep , Sakai, OpenACS. We analyzed each management system and found out how they differ, what software is needed to install the platform. For a visual example, we have inserted an image of each learning management system so that when describing it, we can see a real picture of the software. Visualization helps inform readers about the program. This made it possible to identify the advantages and disadvantages of modern learning management systems, develop a number of recommendations for improving the use of learning management systems. In our scientific work, we have systematized all learning management programs in a table. This allowed us to show them, compare them, and determine which one is the most effective. In general, it can be noted that the development and implementation of modern learning management systems is certainly one of the important issues of education, since they are a modern and effective means of ensuring the integrity and accessibility of training. This is especially true in recent years, when distance learning has become widespread. The transition to online learning is due to the spread of coronavirus infection. This situation was the impetus for the development of online learning platforms.